THE DIFFERENT GRADE OF DEVELOPMENT OF INFANTS GIVEN EXCLUSIVE AND NON EXCLUSIVE BREASTFEEDING IN THE WORKING REGION PUSKESMAS PADANG KARAMBIA PAYAKUMBUH SOUTHERN DISTRICT - Sakinah, Nur; Andayani, Ni Luh Nopi; Dinata, I Made Krisna (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 3 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i03.p11, 2018)
ABSTRACT Development refers to change or growth that occurs in a child during the life span from birth to adolescence. This change occurs in an orderly sequence, involving, physical, cognitive, and emotional development. The research was aimed to determine the effect of breastfeeding differences on the grade of infant development. The research was also aimed to prove the different grade of development of infants given exclusive breastfeeding and non exclusive. This research is analytics observational with cross sectional approach and total sampling as sampling technique. Development were seen using a pre-screening developmental questionnaire (KPSP) with charging directly by respondents accompanied by researchers. The results of a questionnaire be consider to be normal, suspect and delay interpretation. The result of research among 30 people (19 people each of exclusive breastfeeding and 21 people for non exclusive breastfeeding) showed that there is no difference in the development of breastfed infants exclusive and non exclusive using chi-square test with the result p=1 or p > 0,05. Keywords: Development, Breast Feeding